2022
DOI: 10.1158/1535-7163.mct-21-0590
|View full text |Cite
|
Sign up to set email alerts
|

[89Zr]ZrDFO-CR011 PET Correlates with Response to Glycoprotein Nonmetastatic Melanoma B–targeted Therapy in Triple-negative Breast Cancer

Abstract: There is a need for prognostic markers to select patients most likely to benefit from antibody–drug conjugate (ADC) therapy. We quantified the relationship between pretreatment PET imaging of glycoprotein nonmetastatic melanoma B (gpNMB) with 89Zr-labeled anti-gpNMB antibody ([89Zr]ZrDFO-CR011) and response to ADC therapy (CDX-011) in triple-negative breast cancer. First, we compared different PET imaging metrics and found that standardized uptake values (SUV) and tumor-to-heart SUV ratios were sufficient to d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For all these trials, there are only two main types of OS: soft and solid, as observed in the table. The following active pharmaceutical ingredients (API) are appropriate for OS: topotecan (Tpt) [45], pazopanib (Pzp) [46], placebo (Plb) [47], gemcitabine (Gct) [48], M6620 [49][50], regorafenib (Rgf) [51][52], glembatumumab vedotin (GV) [53][54], lenvatinib [55], etoposide and ifosfamide (EnI) [56], nab-rapamycin (Rpm) [57][58], cyclophosphamide (Cfa) [59], simvastatin (Sim) [60], myeloid growth factor (MGF) [61], nab-paclitaxel [62][63], methotrexate (Mtx) [64], and doxorubicin (Dox) [65]. Besides, the primary tests, such as laboratory biomarker analyses [66] and dose escalation studies [67], were conducted for these successful triumphs.…”
Section: Clinical Advancementmentioning
confidence: 99%
“…For all these trials, there are only two main types of OS: soft and solid, as observed in the table. The following active pharmaceutical ingredients (API) are appropriate for OS: topotecan (Tpt) [45], pazopanib (Pzp) [46], placebo (Plb) [47], gemcitabine (Gct) [48], M6620 [49][50], regorafenib (Rgf) [51][52], glembatumumab vedotin (GV) [53][54], lenvatinib [55], etoposide and ifosfamide (EnI) [56], nab-rapamycin (Rpm) [57][58], cyclophosphamide (Cfa) [59], simvastatin (Sim) [60], myeloid growth factor (MGF) [61], nab-paclitaxel [62][63], methotrexate (Mtx) [64], and doxorubicin (Dox) [65]. Besides, the primary tests, such as laboratory biomarker analyses [66] and dose escalation studies [67], were conducted for these successful triumphs.…”
Section: Clinical Advancementmentioning
confidence: 99%
“…The cell line MDA-MA-468 was chosen due to its moderate expression of gpNMB; whereas, MDA-MB-231 was selected because it does not express gpNMB and was used as a negative control [18]. The IC50 value for dasatinib was first determined in vitro to select an appropriate dose for the treatment of cells, where the IC50 was determined to be 2.25 μM (Fig S1A).…”
Section: Dasatinib Treatment Upregulates Gpnmb Expression In Mda-mb-4...mentioning
confidence: 99%
“…Positron emission tomography (PET) imaging is a noninvasive imaging modality that has potential to predict which patients are likely to respond to treatment by determining relative expression of therapeutic targets prior to treatment [18][19][20]. ImmunoPET combines the specificity of antibodies with the sensitivity of PET imaging to detect antigen biomarkers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations